2022
DOI: 10.1002/dac.5187
|View full text |Cite
|
Sign up to set email alerts
|

An effective combination of terahertz band NOMA and MIMO system for power efficiency enhancement

Abstract: Terahertz (THz) band communication is extensively used to reach future communication needs for large capacity. Moreover, the multiple input multiple output (MIMO) and Non-orthogonal multiple access (NOMA) approach with multi-antenna enable users to share more data with good spectrum efficiency.Due to its various applications, different research works are done in MIMO and NOMA. But the existing approach used in NOMA-MIMO has a major limitation in power efficiency. Hence, this research work is presented for maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Terahertz (THz) communication is becoming more popular, providing a high-speed data rate and a frequency range between .1 and 10 THz. 10 The THz band have a magnitude order of 3 to 4, which is much greater than the present WC band. These bands are highly recommended in mobile phones' capability of effectively providing larger bandwidth.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Terahertz (THz) communication is becoming more popular, providing a high-speed data rate and a frequency range between .1 and 10 THz. 10 The THz band have a magnitude order of 3 to 4, which is much greater than the present WC band. These bands are highly recommended in mobile phones' capability of effectively providing larger bandwidth.…”
Section: Introductionmentioning
confidence: 64%
“…Terahertz (THz) communication is becoming more popular, providing a high‐speed data rate and a frequency range between .1 and 10 THz 10 . The THz band have a magnitude order of 3 to 4, which is much greater than the present WC band.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum efficiency of conventional OMA techniques like frequency division multiple access (FDMA) and time division multiple access (TDMA) is low when users with poor channel quality are utilizing the available bandwidth 3 . Nonetheless, users of NOMA systems communicate at the same frequency, time, and code while using different power levels 4 . It has been demonstrated that by using linear superposition coding (SC), one can obtain the capacity region of degraded single input single output (SISO) Gaussian broadcast channels (BCs) 5,6 …”
Section: Introductionmentioning
confidence: 99%